1999
DOI: 10.1021/jp9901085
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Interactions in Conjugated Oligothiophenes. 3. Optical and Photophysical Properties of Quaterthiophene and Substituted Quaterthiophenes in Various Environments

Abstract: A detailed analysis of the optical and photophysical properties of 2,2‘:5‘:2‘ ‘:5‘ ‘,2‘ ‘‘-quaterthiophene (QT), 3,3‘ ‘‘-dimethoxy-2,2‘:5‘:2‘ ‘:5‘ ‘,2‘ ‘‘-quaterthiophene (DMOQT), 3,3‘ ‘‘-dimethyl-2,2‘:5‘:2‘ ‘:5‘ ‘,2‘ ‘‘-quaterthiophene (DMQT) and 3‘,4‘ ‘-didecyl-2,2‘:5‘:2‘ ‘:5‘ ‘,2‘ ‘‘-quaterthiophene (DDQT) in various environments is reported. In solution at room temperature, the optical properties of the free molecules are obtained and discussed in terms of the effect of the substitution on the conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
75
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 42 publications
8
75
2
Order By: Relevance
“…On the other hand, as observed with poly(3,3'-dialkyl-2,2'-bithiophene)s ( possible by the adequate steric hindrance created by the methyl group at the 4-position, which forces the formation of a nonplanar conformation when highly conjugated (coplanar) polythiophene assemblies are disrupted [66][67][68]. Recent calculations and experimental studies on oligomeric model compounds are in agreement with this model and have also indicated that the chromic effects in neutral substituted polythiophenes could be mainly due to conformational changes instead of excitonic effects [69][70][71]. However, important excitonic effects may take place in polydiacetylenes and unsubstituted oligothiophenes [69][70][71][72][73].…”
Section: Thermochromism and Structural Aspectsmentioning
confidence: 64%
“…On the other hand, as observed with poly(3,3'-dialkyl-2,2'-bithiophene)s ( possible by the adequate steric hindrance created by the methyl group at the 4-position, which forces the formation of a nonplanar conformation when highly conjugated (coplanar) polythiophene assemblies are disrupted [66][67][68]. Recent calculations and experimental studies on oligomeric model compounds are in agreement with this model and have also indicated that the chromic effects in neutral substituted polythiophenes could be mainly due to conformational changes instead of excitonic effects [69][70][71]. However, important excitonic effects may take place in polydiacetylenes and unsubstituted oligothiophenes [69][70][71][72][73].…”
Section: Thermochromism and Structural Aspectsmentioning
confidence: 64%
“…This concentration dependence is thought to be due to excited-state molecules aggregating more readily than those in the ground state, giving rise to excimeric species. [25,27,28] The emission spectra of the dimers (at low concentration, Figure 6; Supporting Information, Table S3) show a highenergy band at similar energy to the emission (Supporting Information, Table S2) attributed to the thienyl rings of the starting materials. This implies that there is no increase in the delocalization of electronic density upon dimerization, and it is consistent with a twisted conformation in dilute solutions (Scheme 3A).…”
Section: Photophysical Measurementsmentioning
confidence: 88%
“…The thermochromism of terthiophenes and quaterthiophenes has been reported by Cesare et al in a series of papers. [16][17][18] The thermochromism in substituted terthiophenes is coupled with the conformational changes in contrast to the unsubstituted terthiophene which shows an important excitonic effect.…”
Section: Introductionmentioning
confidence: 99%